Creativity in Narrative Writing: Utilizing Mind Mapping with Ethnic Identification Model in Higher Education - Febriani, Suci Ramadhanti; Widayanti, Rizka; Rahmawati, Rahmawati; Sartika, Dewi; Setiawan, Indil; Yolanda, Refiyana; Guettaoi, Kddour Bedra (Universitas Islam Negeri Raden Intan Lampung, 2024)
Arabic language learning innovations are developing with various learning media, such as mindmapping. The use of mindmapping-based media can provide learning experiences for students. This research aimed to test the effectiveness of Mind Mapping concept in narrative writing skills for ethnic groups in Indonesia. A mixed research design was used with a quantitative approach to test the effectiveness of learning writing skills using Mind Mapping and a qualitative approach to identify student creativity in developing narrative paragraphs. 35 students who studied writing skills at UIN Imam Bonjol Padang in the Arabic Language Education study program were involved. The results showed that; 1) The effectiveness of Mind Mapping in narrative writing showed an increase in the average learning outcomes for writing skills to 77.91 which showed positive significance; 2) Creativity in writing narratives about Indonesian ethnic groups was identified including the distribution of the meaning of ethnic groups, characteristics of ethnic groups and examples of traditional culture, characterized by varied writing structures with the choice of various grammatical structures such as the arrangement of verbal phrases, adjectives, prepositions, adverbial attributes and nominal phrases. This article confirmed that the use of Mind Mapping for learning writing skills can develop paragraph ideas for writing skills in higher education.